Pelvic Floor Muscule Exercise (PEME) Terhadap Fungsi Traktus Urinarius (MIKSI) pada Lansia - Keristina Ajul; Lilik Pranata; Aniska Indah Fari; Veroneka Yosefpa Windahandayani; Sri Indaryati (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Urinary or micturition problems in the elderly often occur and greatly interfere with daily activities so that they can affect the lifestyle and health of the elderly, the purpose of this study was to see the effect of Pelvic Floor Muscule Exercise (PFME). Elderly is a continuation of a life process that is characterized by changes and decreases in the ability of body functions, one of which is urinary function and gastrointestinal function. The aim of the study was to analyze differences in pelvic floor muscular exercise (PFME) on the function of the urinary tract (micturition) in the elderly. The research method used was quantitative with a pre-experimental design. The number of samples is 21 respondents. The results of the study. The function of the urinary tract (voiding) before the intervention was 29.20 with a standard deviation of 2.530, while the average value after the intervention was 45.90 with a standard deviation of 6.790. The results of the T test (paired samples test) on the urinary tract (micturition) obtained p value = 0.000 which means that there is a significant effect on the urinary tract (voiding) before and after the PFME intervention is given, this shows the p value < (0 ,05). This shows that PFME activities need to be carried out regularly and continuously in order to have a more meaningful impact on benefits, so as to reduce micturition disorders in the elderly.